2016
DOI: 10.4103/0970-9185.188830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of block characteristics of spinal anesthesia following intravenous dexmedetomidine and clonidine

Abstract: Background and Aims:Different routes of administration of α2 adrenergic receptor agonists have been found to prolong the duration of spinal block.Material and Methods:One hundred and twenty patients, aged 18-60 years, of ASA physical status I or II posted for elective fixation of fractures of lower limb under spinal anesthesia were selected. Spinal anesthesia was administered with 2.5 ml of 0.5% bupivacaine mixed with 10 μg fentanyl. The patients were randomized to receive intravenous (IV) dexmedetomidine 1 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…As a result, the initiation of surgery was faster, and it was easier to administer sufficient anesthesia. In a similar study, Agrawal et al [25] demonstrated that IV dexmedetomidine prolonged the duration of blockade in patients administered spinal anesthesia.…”
Section: Discussionmentioning
confidence: 89%
“…As a result, the initiation of surgery was faster, and it was easier to administer sufficient anesthesia. In a similar study, Agrawal et al [25] demonstrated that IV dexmedetomidine prolonged the duration of blockade in patients administered spinal anesthesia.…”
Section: Discussionmentioning
confidence: 89%
“…Patients who received SC dexmedetomidine or clonidine as adjuvants to SAB required significantly less analgesia in the postoperative period in contrast to patients who received SAB alone. Agarwal et al3 compared IV dexmedetomidine infusion versus IV clonidine infusion as adjuvant to SAB. They found that patients who received either of the two drugs intraoperatively required significantly lower doses of rescue analgesic agents in the postoperative period when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha 2 adrenergic agonists have both analgesic and sedative properties when used as adjuvants to SAB. They act at spinal and supra spinal levels of the central nervous system (CNS) to modulate pain relief 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of postoperative anaesthesia was longer in Dexmedetomidine group. They arrived at the conclusion that better conditions were achieved as a result of using Dexmedetomidine [ 15 ]. In the present research, Fentanyl yielded a longer period of anaesthesia with less drug needed after the operation.…”
Section: Discussionmentioning
confidence: 99%